Dissociation of somatic growth, time of sexual maturity, and life expectancy by overexpression of an RGD‐deficient IGFBP‐2 variant in female transgenic mice. Issue 1 (28th October 2015) - Hoeflich, Andreas; Reyer, Anja; Ohde, Daniela; Schindler, Nancy; Brenmoehl, Julia; Spitschak, Marion; Langhammer, Martina; Tuchscherer, Armin; Wirthgen, Elisa; Renner‐Müller, Ingrid; Wanke, Rüdiger; Metzger, Friedrich; et al.
Summary: Impaired growth is often associated with an extension of lifespan. However, the negative correlation between somatic growth and life expectancy is only true within, but not between, species. This can be observed because smaller species have, as a rule, a shorter lifespan than larger species. In insects and worms, reduced reproductive development and increased fat storage are associated with prolonged lifespan. However, in mammals the relationship between the dynamics of reproductive development, fat metabolism, growth rate, and lifespan are less clear. To address this point, female transgenic mice that were overexpressing similar levels of either intact (D‐mice) or mutant insulin‐like growth factor‐binding protein‐2 (IGFBP‐2) lacking the Arg‐Gly‐Asp (RGD) motif (E‐ mice) were investigated. Both lines of transgenic mice exhibited a similar degree of growth impairment (−9% and −10%) in comparison with wild‐type controls (C‐mice). While in D‐mice, sexual maturation was found to be delayed and life expectancy was significantly increased in comparison with C‐mice, these parameters were unaltered in E‐mice in spite of their reduced growth rate. These observations indicate that the RGD‐domain has a major influence on the pleiotropic effects of IGFBP‐2 and suggest that somatic growth and time of sexual maturity or somatic growth and life expectancy are less closely related than thought previously.